Accumulation of current-use pesticides, cholinesterase inhibition and reduced body condition in juvenile one-sided livebearer fish (Jenynsia multidentata) from the agricultural Pampa region of Argentina - Brodeur, Celine Marie Julie; Sanchez, Marisol; Castro, Luciana; Cristos, Diego Sebastian; Rojas, Dante Emanuel; Damonte, María Jimena; Poliserpi, María Belén; D'Andrea, María Florencia; Andriulo, Adrian Enrique (2018)
The aim of this study was to characterize the level and nature of the pesticide contamination received by one-sided livebearer fish (Jenynsia multidentata) from a watercourse situated within the main agricultural region of Argentina, and to assess the effects of this contamination on fish health. Juvenile onesided livebearer fish (Jenynsia multidentata) were collected in December 2011 and March 2012 from three sites along the Pergamino River. Pesticide contamination was characterized by extracting whole fish and analytically determining thirty different pesticide molecules. The biomarkers catalase, glutathione-S-transferase, and cholinesterases were assessed. Body condition was calculated as an estimate of the amount of energy reserves possessed by the fish. Seventeen different pesticides were detected in fish tissues with 81% of captured animals containing at least one pesticide molecule. The pyrethroid insecticides fenvalerate and bifenthrin were most frequently detected, being respectively found in 41.8 and 36.4% of samples tested. Highly toxic dichlorvos and pirimiphos-methyl were detected. Differential levels of contamination could not be established amongst sites but were observed within sites amongst the two sampling dates. The months when pesticide residues were most abundant from in Site A and B corresponded to the months when body condition was at its lowest in the two sites. The inhibition of Che activity in March when body condition was reduced also points to a role of insecticide contamination in the reduction of body condition. These findings provide strong new evidence that current-used agricultural pesticides can accumulate in wild fish and impact their health and energetics.